2007
DOI: 10.1590/s1413-35552007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Teste de caminhada de seis minutos em diferentes faixas etárias e índices de massa corporal

Abstract: Introduction: Submaximal tests have been chosen to evaluate functional status because of their practicality and low cost. Objective: To correlate the distance walked during a six-minute test with age and body mass index, and to verify the need for applying a second test. Method: 122 healthy Brazilians aged between 18 and 80 years who had a sedentary lifestyle performed two tests that consisted of walking as far as possible over a six-minute period. Their weights and heights were assessed by calculating the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
34

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 10 publications
(18 reference statements)
3
28
0
34
Order By: Relevance
“…This result corroborate with studies conducted on the Brazilian and American population 22,24 . This result suggest that there is a decrease in physical capacity of the elderly over time.…”
Section: Discussionsupporting
confidence: 92%
“…This result corroborate with studies conducted on the Brazilian and American population 22,24 . This result suggest that there is a decrease in physical capacity of the elderly over time.…”
Section: Discussionsupporting
confidence: 92%
“…Several recent studies [2][3][4] have focused on evaluating and regaining functional capacity or preventing its decline, particularly in older adults 5,6 . The significant increase in the prevalence of chronic degenerative diseases in older adults 7 , especially systemic hypertension or high blood pressure (HBP) which is closely associated with the decline in functional capacity 8,9 , has created the need to study evaluation methods for ADL performance.…”
Section: Introductionmentioning
confidence: 99%
“…The significant differences between the groups regarding the distance covered during the 6MWT suggested that active individuals had higher physical capacities, corroborating previous reported findings with the elderly 26 . From the functional point of view, the 6MWT is widely used for the evaluation of physical fitness and exercise capacity with various populations 43 and consists of a simple and practical test, that can be widely used within clinical contexts. Moderate correlations were observed between the distances covered during the 6MWT and the AAS, which demonstrated that they assessed similar aspects.…”
Section: Discussionmentioning
confidence: 99%